2000
DOI: 10.1016/s0140-6736(00)82038-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer

Abstract: Lung cancer remains a major worldwide health problem, accounting for more than a sixth of cancer deaths. The proportion of cancers that are adenocarcinomas is increasing in North America and to some degree in Europe, leading to a changing clinical picture characterised by early development of metastases. Newer diagnostic techniques have allowed for more accurate tumour staging and treatment planning. In patients with non-small-cell cancer, surgical resection offers substantial cure rates in early-stage cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
416
2
13

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(435 citation statements)
references
References 40 publications
4
416
2
13
Order By: Relevance
“…The current treatment strategies for advanced lung cancer include surgical resection, radiation, cytotoxic chemotherapy, and photodynamic therapy (5). In almost two thirds of cases, the cancer has already spread beyond localized disease at the time of diagnosis, limiting therapeutic options (23,24). Therefore, the exploration and development of more effective chemopreventive/chemotherapeutic agents and therapies that can target the molecules associated with tumor proliferation, angiogenesis, and apoptosis resistance will lead to improved outcomes in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment strategies for advanced lung cancer include surgical resection, radiation, cytotoxic chemotherapy, and photodynamic therapy (5). In almost two thirds of cases, the cancer has already spread beyond localized disease at the time of diagnosis, limiting therapeutic options (23,24). Therefore, the exploration and development of more effective chemopreventive/chemotherapeutic agents and therapies that can target the molecules associated with tumor proliferation, angiogenesis, and apoptosis resistance will lead to improved outcomes in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Novel chemotherapeutic agents have been shown in some studies to increase survival of stage IIIB/ IV patients. However, these patients were cured rarely, if ever, by current chemotherapeutic agents (Hoffman et al, 2000). On the other hand, several phase III studies have shown that cisplatincontaining induction chemotherapy may increase survival rate in stage IIIA or IIIB locally advanced non-small cell lung cancer (LAD-NSCLC) patients.…”
mentioning
confidence: 99%
“…In the leukocytes, pStat1 increased modestly (\1.5-fold) with IFN-c treatment (data was not shown). The clinico-pathologic characteristics of Patients A and B were listed in Table 1 Different Patterns of Stat1 Activation in Cancer Cells from MPE had Different Sensitivities to Cisplatin Cisplatin was the main agent for treating advanced lung cancer (10). Because Stat1 activation might contribute to drug resistance of cancer cells (16,17), the relationship between Stat1 activation after IFN-c stimulation and cell sensitivity to cisplatin in cancer cells from MPEs was investigated.…”
Section: Scpfc and Western Blot Analysis Of Ifn-c-induced Stat1 Phospmentioning
confidence: 99%
“…Lung cancer is frequently complicated by malignant pleural effusion (MPE) (10). Clinically, MPE is easily recurrent and difficult to manage (11,12).…”
mentioning
confidence: 99%